Incidence And Outcome of Acute Kidney Injury in Critically ill Children at Dr. Soetomo Hospital Surabaya (Bangladesh Journal of Child Health, 2015)
Background: The development of acute kidney injury (AKI) in critically ill patients, or AKI children worsened to be critically ill, is associated with increased morbidity and mortality. Early detection on AKI improves its poor outcome in those children. To study the incidence and correlate the outcome of critically ill children with AKI in children admitted to Pediatric Intensive Care Unit (PICU) at Dr. Soetomo Hospital Surabaya. Methodology: We prospectively studied children admitted to PICU during 15 January to 14 April 2014. Demographic data including age and sex, PICU indications, and AKI staging were recorded. All data were analyzed by descriptive statistics and chi-square test (P